QOLP-25. BASELINE QUALITY OF LIFE BURDEN IN PATIENTS WITH CENTRAL NERVOUS SYSTEM (CNS) TUMOURS TREATED WITH PENCIL BEAM PROTON THERAPY AT INDIA'S FIRST PROTON THERAPY CENTRE. (9th November 2020) - Jalali, Rakesh; Chilukuri, Srinivas; Kumar, Roopesh; Nangia, Sapna; Panda, Pankaj Kumar
Abstract: The aim of this study is to evaluate and assess the impact of baseline quality of life (QOL) in adult patients with central nervous system (CNS) tumours treated with pencil beam proton therapy (PT) seen consecutively at India's first proton therapy centre. Data sets of 50 consecutive adult patients with histologically proven brain neoplasms (both primary and recurrent) who were planned for proton therapy at our centre were during one full calendar year were considered for this study. The study included detailed neurological assessment, evaluation of QOL using EORTC questionnaire (QLQ-C30) and specific Brain Cancer module (BN20). In the present analysis, QOL scores before starting adjuvant treatment were measured and impact of patient and tumour related factors were analysed. Baseline global QOL data of all patients (available in 50) was 58.3 which is relatively low including in all histological tumour types. Physical function, role function, emotion function, cognitive and social function scores were 77.9, 80, 78.5, 80.3, 69.3 (higher values better), respectively. Domains of visual disorder, motor deficit, communication deficit, headache, seizures and drowsiness scores were 21.5, 20.3, 32.3, 31, 20.4, 32.6 and 14.5 (lower values better), respectively. Elderly patients (> 50 years) had poorer global score (p < 0.05). Patients with lower performance status (KPS < 70) had a lower global QOL (KPS > or = 80 vs. < or= 70; 42 vs. 75; p < 0.05) including in all histological types of high-grade gliomas (HGG) (HGG vs. LGG; 67 vs. 59; p < 0.05). Patients undergoing re-irradiation had poorer global score as compared to ones who had not received any radiation previously (p < 0.05). Patients with malignant, recurrent tumours, poor performance status and patients who had previously been irradiated had significantly lower QOL scores even before starting adjuvant treatment.